Akkermansia muciniphila and its role in regulating host functions. (May 2017) - Derrien, Muriel; Belzer, Clara; de Vos, Willem M.
Abstract: Akkermansia muciniphila is an intestinal bacterium that was isolated a decade ago from a human fecal sample. Its specialization in mucin degradation makes it a key organism at the mucosal interface between the lumen and host cells. Although it was isolated quite recently, it has rapidly raised significant interest as A. muciniphila is the only cultivated intestinal representative of the Verrucomicrobia, one of the few phyla in the human gut that can be easily detected in phylogenetic and metagenome analyses. There has also been a growing interest in A. muciniphila, due to its association with health in animals and humans. Notably, reduced levels of A. muciniphila have been observed in patients with inflammatory bowel diseases (mainly ulcerative colitis) and metabolic disorders, which suggests it may have potential anti-inflammatory properties. The aims of this review are to summarize the existing data on the intestinal distribution of A. muciniphila in health and disease, to provide insight into its ecology and its role in founding microbial networks at the mucosal interface, as well as to discuss recent research on its role in regulating host functions that are disturbed in various diseases, with a specific focus on metabolic disorders in both animals and humans. Highlights: Akkermansia spp. are widely present in the intestinal tract of man and other animals. A. spp. have been negatively associated with metabolic disorder in many clinical and preclinical studies. Enrichment of Akkermansia following dietary or drug supplementation frequently coincides with improved metabolic parameters. When administered alive, Akkermansia muciniphila protects mice from diet-induced obesity.